Parâmetros acústicos, perceptivo-auditivos, eletroglotográficos, aerodinâmicos e laríngeos da voz de cantores disfônicos: análise do efeito imediato do Lax Vox® - Ruliano Santana da Matta (2020)
Introduction: The voice plays an important role in human communication and demonstrates emotional aspects of our personality. The singer is a voice professional who has high demands and vocal complexity, having as characteristics a great vocal adjustments variability that depends on the singing style, and are related to the individual anatomical and physiological singer variations. The dysphonia speech therapy treatment can be performed directly or indirectly. Within the direct approach, the Semi occluded Vocal Tract Exercises (SOVTE) stand out, which consist of partial occlusion of the oral cavity promoting a retroflex resonance, that is, the energy produced by the vocal folds vibration that returns to the glottis and promotes the expansion of the vocal tract, reducing their collision. Lax Vox® is an SOVTE widely used by singers, and studies that analyze its effect in a multidimensional way are important to expand the knowledge about the immediate benefits of using this vocal technique in the voice of dysphonic singers. Purpose: To evaluate the effect of the Lax Vox® vocal technique on acoustic, perceptual-auditory, aerodynamic and electroglottographic parameters in the voice and in the larynx of dysphonic singers. Methods: This is an almost-experimental comparative study between subjects. The study was approved by COEP-UFMG under number 73545417.7.0000.5149. Thirty singers were evaluated, 13 male and 17 female, aged between 18 and 55 years. The inclusion criteria were professional and amateur singers of both sexes who presented vocal complaints, defined by an equal to or greater value than 16 points on the Vocal Symptoms Scale (VSS). The individuals using any type of systemic medication were excluded; with laryngeal changes of neurological origin; pregnant, premenstrual or menstrual women and patients with airway infection. All participants went through vocal assessment through perceptual-auditory, acoustic, aerodynamic and electroglottographic analysis of the voice, and laryngeal assessment using high-speed video laryngoscopy. The research participants were assessed at two points: 1) at the beginning of the collection; and 2) after five minutes of performing the Lax Vox® vocal technique. The acoustic analysis of the voices was performed using the Kay Pentax® CSL program, model 6103, module MDVP. The participants were standing with their feet slightly apart, with the microphone supported by a pedestal at the mouth height and at 10 cm away and performed the sustained emission of the vowel /a/ in a habitual and full way for three seconds. For the auditory-perceptual analysis, in addition to the vowel /a/ the chained speech of the days of the week was performed, all the voices were randomized with the three recording moments and were presented to four speech therapists. For the voices electroglottographic (EGG) evaluation, the Electroglottography module of the Kay Pentax® CSL program, model 6103, was used. The participants were instructed to position themselves in a seated position, then, two surface electrodes were placed in the thyroid cartilage wings, and fixed on the neck with an elastic band, immediately after the participants emitted the vowel /a/ in a habitual and full way and an analysis of the closing quotient was made. For laryngeal evaluation, the High-Speed Video Laryngoscopy (HSV) exam was used, with the Kay Pentax® SL equipment, model 6103. The exams were performed by an otorhinolaryngologist, during the exam the subject was instructed to breathe naturally, performing, then, the emissions of the vowel /a/ and /i/ in the usual fundamental frequency (F0). The data statistical analysis was carried out using the statistical program MINITAB version 17. The variables descriptive analyzes were carried out through the distribution of absolute and relative frequency of the categorical variables and measures of numerical synthesis of the quantitative variables, the intra-evaluator agreement was performed using the AC1 statistic from the statistical program R, in the group comparison, the Student's Paired T test and the Wilcoxon test were used. Results: In the acoustic analysis there was an increase in the men F0 after using the vocal technique Lax Vox® and in women there were no significant changes. In the aerodynamic evaluation, the average values of airflow during vocalization and aerodynamic power increased after using the Lax Vox® vocal technique in both groups of dysphonic singers. There were no significant changes in both genders in the auditory-perceptual assessment, in the larynx visual assessment and in electroglottographic measurements. Conclusion: The Lax Vox® vocal technique in the voice of dysphonic singers has an immediate effect on the increase in F0 in men. In the aerodynamic parameters in both sexes, there was an increase in the air flow and in the aerodynamic power measurements.